APPLICATION OF COOPERATIVE LEARNING MODEL TEAM GAMES TURNAMENT (TGT) TYPE USING MONOPOLY GAME MEDIA IN SOLAR TATA MATERIALS TO IMPROVE GEOGRAPHY LEARNING OUTCOMES CLASS X STUDENTS OF HIGH SCHOOLS - Gregorius Agung Malik (Journal Learning Geography, 2020)
The aimed of this study is to determine the differences between the students’ learning outcomes in geography taught through the Team Games Tournament (TGT) cooperative learning model using monopoly game media and students taught through the Student Teams-Achievement Division (STAD) cooperative learning model on the subject matter of hydrocarbon compounds class X high school students. Data collection was carried out for two (2) months, namely from 20 October 2019 to 25 November 2019. The research method used was quasi-experimental research. The study population was all grade X high school students. Samples were randomly selected and obtained class X5 as an experimental class totaling 35 students and class X6 as a control class totaling 30 students. Student learning outcomes data obtained using written tests. Measurements are based on scores obtained by students based on written test results. Data were analyzed using descriptive and inferential statistical techniques with t-test. T-test results obtained are –ttabel= -1,669 thitung = 3,39ttabel = 1,6720 with a significance level of 0.05. The conclusion from the research results that there is a significant difference between the learning outcomes of students taught through the cooperative learning model Team Games Tournament (TGT) using monopoly game media with student learning outcomes taught through the Student Teams-Achievement Division (STAD) cooperative learning model in the STAD class X high school students. 2017/2018 school year. N-Gain shows that the increase in learning outcomes in the experimental class and the control class are in the medium category that is 0.57 and 0.40. Student learning outcomes taught through the Team Games Tournament (TGT) type of cooperative learning model using monopoly game media are higher than student learning outcomes taught through the Student Teams-Achievement Division (STAD) cooperative learning model.Penelitian ini bertujuan untuk mengetahui perbedaan antara hasil belajar geografi siswa yang diajar melalui model pembelajaran kooperatif tipe Team Games Tournament (TGT) menggunakan media permainan monopoli dengan siswa yang diajar melalui model pembelajaran kooperatif tipe Student Teams-Achievement Division (STAD) pada materi pokok senyawa hidrokarbon siswa kelas X SMA. Pengumpulan data dilakukan selama dua (2) bulan, yaitu dari tanggal 20 Oktober 2019 sampai dengan tanggal 25November 2019. Metode penelitian yang digunakan adalah penelitian eksperimen semu. Populasi penelitian adalah semua siswa kelas X SMA. Sampel dipilih secara acak dan diperoleh kelas X5 sebagai kelas eksperimen berjumlah 35 siswa dan kelas X6 sebagai kelas kontrol berjumlah 30 siswa. Data hasil belajar siswa diperoleh dengan menggunakan tes tertulis. Pengukuran didasarkan pada skor yang diperoleh siswa berdasarkan hasil tes tertulis. Data dianalisis dengan menggunakan teknik statistik deskriptif dan inferensial dengan uji-t. Diperoleh hasil uji-t yaitu –ttabel = -1,669 thitung = 3,39 ttabel = 1,6720 dengan taraf signifikasi sebesar 0,05. Kesimpulan dari hasil penelitian bahwa terdapat perbedaan yang signifikan antara hasil belajar siswa yang diajar melalui model pembelajaran kooperatif tipe Team Games Tournament (TGT) menggunakan media permainan monopoli dengan hasil belajar siswa yang diajar melalui model pembelajaran kooperatif tipe Student Teams-Achievement Division (STAD)pada siswa kelas X SMA. tahun ajaran 2017/2018. N-Gain menunjukkan bahwa peningkatan hasil belajar pada kelas eksperimen dan kelas kontrol berada pada kategori sedang yaitu 0,57 dan 0,40. Hasil belajar siswa yang diajar melalui model pembelajaran kooperatif tipe Team Games Tournament (TGT) menggunakan media permainan monopoli lebih tinggi dari hasil belajar siswa yang diajar melalui model pembelajaran kooperatif tipe Student Teams-Achievement Division (STAD).